Bladder Paraganglioma in a Patient with Von Hippel-Lindau Syndrome: A Case Report - Dalar, Sevda (Asian Pacific Journal of Cancer Care, 2023)
Background: Paragangliomas are rare neuroendocrine tumors that can be either functional or non-functional. While they can occur in various locations, bladder paragangliomas are exceptionally uncommon. These tumors are sometimes associated with hereditary syndromes, such as Von Hippel-Lindau (VHL) syndrome. Case Presentation: This case report describes a patient with VHL syndrome who presented with a paraganglioma located within the bladder.